Preparation method and application of antibacterial salt-resistant hydrogel / pulverized coal photo-thermal composite material

By preparing antibacterial and salt-resistant hydrogel/coal powder photothermal composite, the energy efficiency reduction problem in seawater desalination system due to microbial adhesion and salt crystallization is solved, the long-term stability and salt resistance of the system are improved, and the long-term stability and salt resistance of the system are achieved. Green application of coal materials.

CN119286046APending Publication Date: 2025-01-10TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460183.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During long-term use, the existing solar interface water evaporation system has reduced working energy efficiency and reduced stability due to seawater microbial adhesion and salt particle crystallization. It is necessary to develop antibacterial and salt-resistant photothermal materials to improve the long-term working efficiency of seawater desalination systems.

Method used

The preparation method of antibacterial and salt-resistant hydrogel/coal powder photothermal composite materials is adopted, and the combination of PHMG-g-starch, polyvinyl alcohol, coal powder and glutaraldehyde is carried out through frozen cross-linking and freeze-thawing treatment. Porous PVA/anti-bacterial starch/coal powder composite hydrogel was prepared, which had antibacterial and salt resistance.

Benefits of technology

It improves the long-term working stability and salt resistance of the material during seawater desalination, extends the service life of the system, and realizes the green and sustainable application of coal materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286046A_ABST
    Figure CN119286046A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an antibacterial salt-resistant hydrogel / pulverized coal photo-thermal composite material, and belongs to the technical field of seawater desalination treatment.The preparation method comprises the following steps that corn starch, polyhexamethylene guanidine hydrochloride PHMG, glycerin and deionized water are mixed and put into an internal mixer to be subjected to melt blending, PHMG-g-starch is obtained, and the PHMG-g-starch is added into the internal mixer to be subjected to melt blending; the preparation method comprises the following steps: uniformly stirring and dissolving lignite powder, PHMG-g-starch and polyvinyl alcohol in deionized water, adding glutaraldehyde and a hydrochloric acid aqueous solution, uniformly stirring, then transferring the solution to a mold to form PVA / antibacterial starch / pulverized coal composite hydrogel, freezing the PVA / antibacterial starch / pulverized coal composite hydrogel with liquid nitrogen, unfreezing with deionized water, and drying to obtain the antibacterial modified lignite powder hydrogel. And repeatedly freezing and thawing to obtain the antibacterial salt-resistant hydrogel / pulverized coal photo-thermal composite material. According to the preparation method and application of the antibacterial salt-resistant hydrogel / pulverized coal photo-thermal composite material, on one hand, the long-time working stability of the material during seawater desalination can be improved, and on the other hand, green and sustainable application of a coal material is expected to be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of seawater desalination treatment, and in particular to a preparation method and application of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material. Background Art

[0002] With the rapid growth of the global population and the rapid development of modern industry, people's demand for clean fresh water resources is also increasing. It is estimated that by 2050, about 5 billion people in the world will face the dilemma of clean water shortage; on the other hand, seawater accounts for 96.5% of the world's water resources. The efficient use of this part of water resources will greatly alleviate the dilemma of water shortage. In recent years, solar interfacial water evaporation technology based on high-efficiency photothermal materials has gradually gained widespread attention due to its advantages of green, low cost and sustainable use.

[0003] However, the current solar interfacial water evaporation systems / materials for seawater desalination face the dilemma of reduced working efficiency during actual long-term use, which is mainly caused by the adhesion of seawater microorganisms and the crystallization of salt particles in the device channels. First of all, since most solar-water evaporation systems adopt a working mode floating on the water surface, the equilibrium temperature under natural light conditions is about 30 to 40°C, which is very suitable for the growth and reproduction of bacteria. As the working time of the material increases, the bacteria will adhere to the surface and channels of the evaporation device, resulting in a decrease in evaporation performance. Thirdly, as water evaporation continues to occur on the surface of the device, the salt concentration at the top of the device gradually increases and even causes salt particles to crystallize in the water transport channel of the device, which, on the one hand, hinders the upward transmission of water from the bottom, and on the other hand, also causes its light absorption effect to decrease, further reducing the long-term working stability of the device. Therefore, it is necessary to develop photothermal materials with both antibacterial and salt-resistant properties to improve the long-term working efficiency of solar-seawater desalination systems. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, which can improve the long-term working stability of the material during seawater desalination on the one hand, and is also expected to achieve green and sustainable application of coal materials on the other hand.

[0005] To achieve the above object, the present invention provides a method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, comprising the following steps: S1. Preparation of PHMG- g -starch; S2, putting the coal block into a planetary ball mill and grinding it into coal powder particles; S3, PHMG- g- Starch, polyvinyl alcohol and coal powder are added to deionized water, mixed, heated and stirred to dissolve, and then glutaraldehyde solution is added to obtain a mixed solution; S4, adding concentrated hydrochloric acid to deionized water and stirring evenly to prepare a hydrochloric acid aqueous solution; S5, mixing the mixed solution in S3 and the hydrochloric acid aqueous solution in S4 to obtain a precursor solution, transferring the precursor solution to a mold for cooling and cross-linking, and then dialyzing to obtain a PVA / antibacterial starch / coal powder composite hydrogel; S6. Freeze the PVA / antibacterial starch / coal powder composite hydrogel with liquid nitrogen, and thaw it with deionized water, and repeat the freeze-thaw process to obtain a porous PVA / antibacterial starch / coal powder composite hydrogel, that is, an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material.

[0006] Preferably, the specific operation of S1 is: corn starch is mixed with polyhexamethyleneguanidine hydrochloride PHMG, glycerol and deionized water and put into an internal mixer for in-situ melt grafting to obtain polyhexamethyleneguanidine hydrochloride grafted corn starch with antibacterial properties, i.e. PHMG- g -starch.

[0007] Preferably, the mass fraction ratio of corn starch, glycerol, deionized water and polyhexamethyleneguanidine hydrochloride (PHMG) in S1 is 66.3:20:8.4:5.3.

[0008] Preferably, the rotation speed of the planetary ball mill in S2 is 500-1000 rpm, the rotation time is 30-60 min, and the particle size of the coal powder obtained by grinding is 0.5 μm-8 μm.

[0009] Preferably, polyvinyl alcohol and PHMG- g - The ratio of starch is one of g:g=4:10, 6:8, 8:6, 10:4 and 12:2, the heating and stirring temperature is 80-95°C, the heating and stirring time is 30-90min, and the glutaraldehyde solution is 1-3ml, and 40-60wt% of glutaraldehyde is dissolved in water to prepare the method.

[0010] Preferably, the amount of the precursor solution and the coal powder is in the following relationship: the amount of the coal powder added to 100 g of the precursor solution is one of 0 g, 0.4 g, 0.8 g, 1.2 g and 1.6 g.

[0011] Preferably, the hydrochloric acid aqueous solution in S4 is prepared by mixing 60-80 μL of 30-40 wt % concentrated hydrochloric acid into 10 g of hydrochloric acid aqueous solution, and the hydrochloric acid aqueous solution is added 5-30 min after the addition of glutaraldehyde.

[0012] Preferably, the cooling cross-linking temperature in S5 is 15-30° C. and the time is 12-36 hours.

[0013] Preferably, in S6, the thawing temperature is 15-30° C., the thawing time is 3-6 h, and the number of freeze-thaw cycles is 6-12 times.

[0014] The present invention provides an application of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material. The antibacterial and salt-resistant hydrogel / coal powder photothermal composite material prepared by the above-mentioned preparation method of the antibacterial and salt-resistant hydrogel / coal powder photothermal composite material is applied to seawater desalination.

[0015] Therefore, the present invention adopts the preparation method and application of the above-mentioned antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, which can improve the long-term working stability of the material during seawater desalination on the one hand, and is also expected to achieve the green and sustainable application of coal materials on the other hand.

[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a preparation method demonstration diagram of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material of the present invention and an application example; Figure 2 It is a preparation method of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material of the present invention and a graph showing the mass change over time of the PVA / coal powder antibacterial and salt-resistant evaporation hydrogel of application examples 1-5; Figure 3 It is a schematic diagram of the antibacterial ability of the PVA / coal powder antibacterial and salt evaporation hydrogel in the preparation method of an antibacterial and salt resistant hydrogel / coal powder photothermal composite material and application example 2 of the present invention; Figure 4 It is a schematic diagram of the salt resistance of the PVA / coal powder antibacterial and salt-resistant evaporative hydrogel of the present invention in the preparation method of the antibacterial and salt-resistant hydrogel / coal powder photothermal composite material and the application example 2; Figure 5 It is a schematic diagram of the long-term stability of the PVA / coal powder antibacterial and salt-resistant evaporation hydrogel of the present invention's preparation method of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material and application example 2. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0019] Unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The words "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0020] Example like Figure 1 As shown, the present invention provides a method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material. Figure 1 PVA is polyvinyl alcohol, PHMG-g-Starch is corn starch grafted with polyhexamethyleneguanidine hydrochloride, and Glutaraldehyde is glutaraldehyde. The process includes the following steps: S1. Preparation of PHMG- g -Starch: corn starch, polyhexamethyleneguanidine hydrochloride (PHMG), glycerol, and deionized water were mixed and put into an internal mixer for in-situ melt grafting to obtain polyhexamethyleneguanidine hydrochloride grafted corn starch with antibacterial properties, namely PHMG- g -starch, corn starch, glycerol, deionized water and polyhexamethyleneguanidine hydrochloride PHMG mass fraction ratio is 66.3:20:8.4:5.3. The extruder screw temperature in the internal mixer is preferably 110, 125 or 135°C, the screw speed is 80rpm, and the in-situ reaction time in the internal mixer is 10min.

[0021] Corn starch, as a thickener and gelling agent, can provide the network structure required for hydrogels and help form stable gels. In water, starch can absorb water and swell. Heating or adding cross-linking agents can promote the formation of physical or chemical cross-links between starch molecules, thereby enhancing the mechanical strength and stability of the gel.

[0022] PHMG is a highly effective broad-spectrum antimicrobial agent that can destroy bacterial cell walls and inhibit microbial growth, thereby giving the composite material excellent antimicrobial properties, which is particularly important for materials that need to be used in humid or easily contaminated environments. Since PHMG is a cationic antimicrobial agent, it can give starch a long-lasting antimicrobial effect after being introduced into starch by melt grafting; on the other hand, after the cationic antimicrobial agent is introduced into the photothermal material, it can generate additional osmotic pressure inside the material when exposed to light, thereby improving the ability to transport water from the bottom upward and improving the salt resistance of the photothermal material. Therefore, the hydrogel composite photothermal material can be used as an ideal material for solar-water evaporation systems.

[0023] As a commonly used humectant, glycerol can absorb and retain water, maintain the water content of the hydrogel, and ensure that the material can still maintain a certain softness and elasticity under dry conditions. At the same time, it can also act as a plasticizer to improve the processing performance and physical properties of the material. By adjusting the content of glycerol, the physical state of the hydrogel, such as viscosity and gel strength, can be controlled to optimize the overall performance of the composite material.

[0024] Deionized water, as a solvent, is an indispensable component in the preparation process. It ensures the purity of the reaction system and avoids the adverse effects of impurity ions on the performance of composite materials. This is especially important for photothermal materials that require high purity and consistency.

[0025] S2. Grind the coal into coal powder particles in a planetary ball mill at a rotation speed of 500-1000rpm and a rotation time of 30-60min. The particle size of the coal powder particles obtained by grinding is 0.5μm-8μm. Compared with traditional photothermal materials, coal powder has lower cost and good light absorption ability. Coal powder can absorb light energy and convert it into heat energy, producing a local warming effect, which is very beneficial for certain application scenarios that require thermal response or sterilization.

[0026] S3, PHMG- g - Starch, polyvinyl alcohol and coal powder are added to deionized water and mixed, heated and stirred to dissolve, and then glutaraldehyde solution is added to obtain a mixed solution; polyvinyl alcohol and PHMG- g - starch ratio is one of g:g=4:10, 6:8, 8:6, 10:4 and 12:2, the heating and stirring temperature is 80-95°C, the time is 30-90min, the glutaraldehyde is preferably added after the above solution is heated and stirred for 1h, and the glutaraldehyde solution is 1-3ml, 40-60wt% of glutaraldehyde is dissolved in water to prepare, wherein PHMG- g -Strain the starch through a sieve into a container.

[0027] PVA is a water-soluble polymer that is often used as the main component of hydrogels. In water, PVA chains form physical crosslinks through hydrogen bond interactions, thereby forming a network structure of the hydrogel, which provides the necessary physical support and shape stability for the composite material. PVA has good hydrophilicity and can absorb a large amount of water, giving the hydrogel good flexibility and water retention capacity, which is essential for maintaining the wet state and activity of the material. The hydroxyl groups (-OH) on the PVA chain can be chemically modified, such as increasing the crosslinking density of the network through crosslinking reactions, thereby improving the mechanical strength and salt resistance of the gel.

[0028] Glutaraldehyde is a bifunctional crosslinking agent that can crosslink with the hydroxyl groups in PVA to form a more stable and durable network structure. This process increases the mechanical strength and chemical resistance of the hydrogel, allowing it to maintain structural integrity in a variety of environments (including salty environments). Glutaraldehyde itself has a certain antibacterial effect. After being fixed in the hydrogel network through a crosslinking reaction, it can continuously release antibacterial components, further enhancing the antibacterial properties of the composite material.

[0029] S4. Add concentrated hydrochloric acid to deionized water and stir evenly to prepare a hydrochloric acid aqueous solution; prepare 10g of hydrochloric acid aqueous solution by mixing 60-80μL of 30-40wt% concentrated hydrochloric acid, and add the hydrochloric acid aqueous solution 5-30min after the addition of glutaraldehyde. In the preparation of composite materials, hydrochloric acid solution is mainly used to adjust the pH value of PVA solution. Appropriate pH conditions can promote the dissolution of PVA, optimize the gelation process, and may affect the efficiency of subsequent chemical reactions (such as cross-linking). For certain reactions that require a specific ionic environment, such as cross-linking reactions, hydrochloric acid can provide the necessary ionic environment to promote the functionalization process of cross-linking agents (such as glutaraldehyde) to enhance the network structure and performance of the material.

[0030] S5, mixing the mixed solution in S3 and the hydrochloric acid aqueous solution in S4 to obtain a precursor solution, transferring the precursor solution to a mold for cooling and cross-linking, the cooling and cross-linking temperature is 15-30°C, the time is 12-36h, and then dialyzing to obtain a PVA / antibacterial starch / coal powder composite hydrogel. The amount of the precursor solution and the coal powder is: the amount of coal powder added in 100g of the precursor solution is one of 0g, 0.4g, 0.8g, 1.2g and 1.6g.

[0031] S6. Freeze the PVA / antibacterial starch / coal powder composite hydrogel with liquid nitrogen and thaw with deionized water at a thawing temperature of 15-30°C for 3-6 hours. Repeat the freeze-thaw process 6-12 times to obtain a porous PVA / antibacterial starch / coal powder composite hydrogel, i.e., an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material.

[0032] Liquid nitrogen freezing causes ice crystals to form rapidly inside the hydrogel, which melt and leave gaps in the subsequent thawing process, forming a porous structure. Porosity is particularly important for hydrogel materials because it can increase the specific surface area of ​​the material, which is conducive to loading more antibacterial agents and improving material exchange efficiency, while also making the heat distribution under the photothermal effect more uniform.

[0033] Freeze-thaw cycles can help redistribute the various components in the composite material (such as polyvinyl alcohol, glutaraldehyde, coal powder, etc.), making the composition of the material more uniform. Appropriate freeze-thaw treatment can enhance the mechanical strength of the hydrogel to a certain extent. The formation and melting of ice crystals can cause the polymer chains to rearrange and form a tighter cross-linked network, thereby improving the toughness of the material.

[0034] The swelling properties of the hydrogel can be adjusted by controlling the number and conditions of freeze-thaw cycles. The porous structure can control the degree of expansion of the material after absorbing water, which helps to maintain structural stability in salt-resistant applications and reduce excessive swelling or shrinkage caused by salt. The deionized water thawing step also helps to replace or remove solvents or impurities that may remain in the material during the previous preparation process, thereby improving the purity and biocompatibility of the composite material.

[0035] Example 1 (1) PHMG- g -Preparation of starch: Dry the corn starch at 80°C for 12 hours to remove moisture. Mix corn starch, glycerol, deionized water, and PHMG at a mass fraction ratio of 66.3:20:8.4:5.3 for 30 minutes, put it in a sealed plastic bag and store it for 2 hours to homogenize the mixture. Subsequently, put the evenly mixed raw materials into an internal mixer and further mix them at a speed of 30r / min until the moisture is removed. The mixing temperature is selected to be 145°C, which is much higher than the reaction temperature of ESO and PHMG (57°C). Then add epoxidized soybean oil with the same mass fraction as PHMG, react in situ for 10 minutes, and discharge and granulate after the torque is stable. Polyhexamethyleneguanidine hydrochloride grafted corn starch particles are obtained, namely PHMG- g -starch.

[0036] (2) Preparation of light absorber coal powder: Select several pieces of lignite purchased from Shanxi Jincheng Anthracite Mining Group Co., Ltd., place them in a mortar and grind them into small particles. Then take them out. Then put them into a JX-4GL planetary grinder, adjust the ball mill speed to 500 rpm, set the operation mode to forward 5 times, reverse 5 times, each rotation lasts 30 minutes, and each stop interval is 1 minute. Keep the ball beads in the ball mill uniformly distributed to obtain coal powder particles with a particle size of 0.5μm-8μm.

[0037] (3) Preparation of PVA / antibacterial starch / coal powder composite hydrogel: First, 2 g of PHMG-g - Starch was added to 18g of water and heated at 90°C to dissolve to obtain solution A. The above solution A was filtered and added to a container, and 12g of PVA and 1.2g of coal powder were weighed, added to water to a total mass of 87g and heated at 90°C to dissolve to obtain solution B. 3ml of glutaraldehyde (50wt% dissolved in water) was added with a dropper. 70μL of hydrochloric acid (36wt% dissolved in water) was pipetted with a pipette to prepare 10g of aqueous solution. After the B solution was mixed evenly, the prepared 10g hydrochloric acid aqueous solution was added for gelation. After gelation for 24h, the obtained gel was immersed in deionized water overnight to obtain a pure hydrogel. The purified hydrogel was frozen with liquid nitrogen, then thawed with deionized water at 30°C for 3h, and the freeze-thaw process was repeated 10 times. After freeze drying, the sample was placed in water to swell again.

[0038] Example 2 The preliminary operation of Example 2 is the same as that of Example 1, and the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is different from that of Example 1. In this embodiment, the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is as follows: first, 4g of PHMG-g-starch is added to 36g of water and heated at 90°C to dissolve to obtain solution A, the above solution A is filtered and added to a container, and 10g of PVA and 1.2g of coal powder are weighed, water is added to a total mass of 87g, and heated at 90°C to dissolve to obtain solution B. 3ml of glutaraldehyde (50wt% dissolved in water) is added with a dropper. 70μL of hydrochloric acid (36wt% dissolved in water) is drawn with a pipette to prepare a 10g aqueous solution. After the B solution is mixed evenly, the configured 10g hydrochloric acid aqueous solution is added for gelation. After gelation for 24h, the obtained gel is immersed in deionized water overnight to obtain a pure hydrogel. The purified hydrogel is frozen with liquid nitrogen, and then thawed with deionized water at a temperature of 30°C for 3h, and the freeze-thaw process is repeated 10 times. After freeze-drying, the samples were placed in water to re-swell.

[0039] Example 3 The preliminary operation of Example 3 is the same as that of Example 1, and the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is different from that of Example 1. In this embodiment, the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is as follows: first, 6 g of PHMG-g-starch is added to 54 g of water and heated at 90°C to dissolve to obtain solution A, the above solution A is filtered and added to a container, and 8 g of PVA and 1.2 g of coal powder are weighed, water is added to a total mass of 87 g, and heated at 90°C to dissolve to obtain solution B. 3 ml of glutaraldehyde (50 wt% dissolved in water) is added with a dropper. 70 μL of hydrochloric acid (36 wt% dissolved in water) is drawn with a pipette to prepare a 10 g aqueous solution. After mixing solution A and solution B evenly, 10 g of the prepared hydrochloric acid aqueous solution is added for gelation. After gelation for 24 hours, the obtained gel is immersed in deionized water overnight to obtain a pure hydrogel. The purified hydrogel is frozen with liquid nitrogen, and then thawed with deionized water at a temperature of 30°C for 3 hours, and the freeze-thaw process is repeated 10 times. After freeze-drying, the samples were placed in water to re-swell.

[0040] Example 4 The preliminary operation of Example 4 is the same as that of Example 1, and the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is different from that of Example 1. In this embodiment, the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is as follows: first, 8 g of PHMG-g-starch is added to 70 g of water and heated at 90 ° C to dissolve to obtain solution A, the above solution A is filtered and added to a container, and 6 g of PVA and 1.2 g of coal powder are weighed, water is added to a total mass of 87 g, and heated at 90 ° C to dissolve to obtain solution B. 3 ml of glutaraldehyde (50 wt% dissolved in water) is added with a dropper. 70 μL of hydrochloric acid (36 wt% dissolved in water) is drawn with a pipette to prepare a 10 g aqueous solution. After mixing solution A and solution B evenly, 10 g of the prepared hydrochloric acid aqueous solution is added for gelation. After gelation for 24 hours, the obtained gel is immersed in deionized water overnight to obtain a pure hydrogel. The purified hydrogel is frozen with liquid nitrogen, and then thawed with deionized water at a temperature of 30 ° C for 3 hours, and the freeze-thaw process is repeated 10 times. After freeze-drying, the samples were placed in water to re-swell.

[0041] Example 5 The preliminary operation of Example 5 is the same as that of Example 1, and the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is different from that of Example 1. In this embodiment, the preparation of the PVA / antibacterial starch / coal powder composite hydrogel is as follows: first, 10 g of PHMG-g-starch is added to 70 g of water and heated at 90 ° C to dissolve to obtain solution A, the above solution A is filtered and added to a container, and 4 g of PVA and 1.2 g of coal powder are weighed, water is added to a total mass of 87 g, and heated at 90 ° C to dissolve to obtain solution B. 3 ml of glutaraldehyde (50 wt% dissolved in water) is added with a dropper. 70 μL of hydrochloric acid (36 wt% dissolved in water) is drawn with a pipette to prepare a 10 g aqueous solution. After mixing solution A and solution B evenly, 10 g of the prepared hydrochloric acid aqueous solution is added for gelation. After gelation for 24 hours, the obtained gel is immersed in deionized water overnight to obtain a pure hydrogel. The purified hydrogel is frozen with liquid nitrogen, and then thawed with deionized water at a temperature of 30 ° C for 3 hours, and the freeze-thaw process is repeated 10 times. After freeze-drying, the samples were placed in water to re-swell.

[0042] Comparative Example 1 10 g of PVA and 1.2 g of coal powder were added to 87 g of water in total. Next, 3 ml of glutaraldehyde and 10 g of dilute hydrochloric acid (3 wt% dissolved in water) were added to the mixture, which was then gelled for 24 h. The resulting gel was immersed in deionized water overnight to obtain a purified gel. Finally, the hydrogel was frozen with liquid nitrogen and thawed with deionized water at 30 °C, and the freeze-thaw process was repeated 10 times. After freeze drying, the sample was rehydrated with water.

[0043] The PVA / antibacterial starch / coal powder composite hydrogels prepared in the above Examples 1-5 and Comparative Example 1 were cut into cubes with a length of 2 cm, a width of 2 cm, and a height of 1 cm, and placed on top of the PS foam. They were then placed in 3.5 wt % salt water, and the evaporation performance of the prepared hydrogel-coal powder composite materials was tested using a CEL-S500 / 350 xenon lamp light source to simulate sunlight.

[0044] like Figure 2 As shown in the figure, the mass change trend of PVA / antibacterial starch / coal powder composite hydrogels with different proportions during the evaporation process is shown. Among them, the evaporation rate of the PVA / coal powder antibacterial and salt-resistant evaporation hydrogel prepared in Example 2 is 2.84 kg m -2 h -1 The PVA / coal powder antibacterial and salt-resistant evaporation hydrogel prepared in Example 2 has a faster evaporation rate and good evaporation performance.

[0045] like Figure 3As shown, the PVA / antibacterial starch / coal powder composite hydrogel prepared in Example 2 has significant antibacterial properties, and has extremely strong antibacterial effects on Escherichia coli and Staphylococcus aureus, with an antibacterial rate of up to 99.9%. In comparison, the PVA-Coal prepared in Comparative Example 1 has no antibacterial effect on Escherichia coli, but may promote bacterial growth; it has a certain antibacterial effect on Staphylococcus aureus, but the effect is not as good as the PVA / antibacterial starch / coal powder composite hydrogel prepared in Example 2. The results show that Example 2 has significant antibacterial properties, while the antibacterial properties of the PVA-Coal prepared in Comparative Example 1 are relatively weak, and there are differences in the antibacterial effects on different bacteria.

[0046] like Figure 4 As shown, the evaporation rate of the PVA / antibacterial starch / coal powder composite hydrogel prepared in Example 2 in 20wt% brine remained stable within 14 days, showing good long-term stability, which is a very important property for the solar interfacial water evaporation system used in a high-salt environment.

[0047] like Figure 5 As shown in the figure, after the salt particles are directly placed on the surface of the PVA / antibacterial starch / coal powder composite hydrogel prepared in Example 2, its water evaporation test effect in a 3.5wt% sodium chloride solution under the irradiation of one sunlight intensity is shown. It can be seen that the salt particles on its surface completely disappear after 1 hour, indicating that it has excellent salt resistance in a high-salt environment.

[0048] In summary, the PVA / antibacterial starch / coal powder composite hydrogel prepared in the embodiment has good antibacterial, salt resistance and evaporation properties, is suitable for seawater desalination, and expands the application of hydrogel in the field of seawater desalination.

[0049] Therefore, the present invention adopts the preparation method and application of the above-mentioned antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, which can improve the long-term working stability of the material during seawater desalination on the one hand, and is also expected to achieve the green and sustainable application of coal materials on the other hand.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, characterized in that: The following steps are involved: S1. Preparation of PHMG- g -starch; S2, putting the coal block into a planetary ball mill and grinding it into coal powder particles; S3, PHMG- g - Starch, polyvinyl alcohol and coal powder are added to deionized water, mixed, heated and stirred to dissolve, and then glutaraldehyde solution is added to obtain a mixed solution; S4, adding concentrated hydrochloric acid to deionized water and stirring evenly to prepare a hydrochloric acid aqueous solution; S5, mixing the mixed solution in S3 and the hydrochloric acid aqueous solution in S4 to obtain a precursor solution, transferring the precursor solution to a mold for cooling and cross-linking, and then dialyzing to obtain a PVA / antibacterial starch / coal powder composite hydrogel; S6. Freeze the PVA / antibacterial starch / coal powder composite hydrogel with liquid nitrogen, and thaw it with deionized water, and repeat the freeze-thaw process to obtain a porous PVA / antibacterial starch / coal powder composite hydrogel, that is, an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material.

2. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 1, characterized in that: The specific operation of S1 is: corn starch is mixed with polyhexamethyleneguanidine hydrochloride PHMG, glycerol and deionized water and put into an internal mixer for in-situ melt grafting to obtain polyhexamethyleneguanidine hydrochloride grafted corn starch with antibacterial properties, namely PHMG- g -starch.

3. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 2, characterized in that: The mass fraction ratio of corn starch, glycerol, deionized water and polyhexamethyleneguanidine hydrochloride (PHMG) in S1 is 66.3:20:8.4:5.

3.

4. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 3, characterized in that: The rotation speed of the planetary ball mill in S2 is 500-1000rpm, the rotation time is 30-60min, and the particle size of the coal powder obtained by grinding is 0.5μm-8μm.

5. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 4, characterized in that: Polyvinyl alcohol and PHMG- g - The ratio of starch is one of g:g=4:10, 6:8, 8:6, 10:4 and 12:2, the heating and stirring temperature is 80-95°C, the heating and stirring time is 30-90min, and the glutaraldehyde solution is 1-3ml, and 40-60wt% of glutaraldehyde is dissolved in water to prepare the method.

6. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 5, characterized in that: The dosage relationship between the precursor solution and the coal powder is: the amount of coal powder added to 100g of the precursor solution is one of 0g, 0.4g, 0.8g, 1.2g and 1.6g.

7. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 6, characterized in that: The hydrochloric acid aqueous solution in S4 is prepared by mixing 60-80 μL of 30-40 wt % concentrated hydrochloric acid into 10 g of hydrochloric acid aqueous solution, and the hydrochloric acid aqueous solution is added 5-30 minutes after the addition of glutaraldehyde.

8. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 7, characterized in that: The cooling cross-linking temperature in S5 is 15-30°C and the time is 12-36h.

9. The method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material according to claim 8, characterized in that: In S6, the thawing temperature is 15-30°C, the thawing time is 3-6h, and the number of freeze-thaw cycles is 6-12 times.

10. An application of an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material, characterized in that: The antibacterial and salt-resistant hydrogel / coal powder photothermal composite material prepared by the method for preparing an antibacterial and salt-resistant hydrogel / coal powder photothermal composite material as described in claim 9 is applied to seawater desalination.